The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1038/sj.npp.1301288
|View full text |Cite
|
Sign up to set email alerts
|

Serial Vagus Nerve Stimulation Functional MRI in Treatment-Resistant Depression

Abstract: Vagus nerve stimulation (VNS) therapy has shown antidepressant effects in open acute and long-term studies of treatment-resistant major depression. Mechanisms of action are not fully understood, although clinical data suggest slower onset therapeutic benefit than conventional psychotropic interventions. We set out to map brain systems activated by VNS and to identify serial brain functional correlates of antidepressant treatment and symptomatic response. Nine adults, satisfying DSM-IV criteria for unipolar or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
95
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(111 citation statements)
references
References 63 publications
12
95
0
3
Order By: Relevance
“…Results of imaging studies in patients with epilepsy or depression who are treated with VNS also show widespread effects on subcortical and cortical regions, with short-term VNS producing increases in blood flow in the hypothalamus, thalamus, and insular cortex but decreases in the hippocampus and posterior cingulate gyrus (Chae et al, 2003). Longterm VNS produced both increased (Kosel et al, 2011) and decreased (Nahas et al, 2007) changes in blood flow in cortical regions although subcortical regions were activated (Henry et al, 2004). Inconsistent results were also obtained in the amygdala (Zobel et al, 2005;Conway et al, 2006).…”
Section: Downloaded Fromsupporting
confidence: 59%
“…Results of imaging studies in patients with epilepsy or depression who are treated with VNS also show widespread effects on subcortical and cortical regions, with short-term VNS producing increases in blood flow in the hypothalamus, thalamus, and insular cortex but decreases in the hippocampus and posterior cingulate gyrus (Chae et al, 2003). Longterm VNS produced both increased (Kosel et al, 2011) and decreased (Nahas et al, 2007) changes in blood flow in cortical regions although subcortical regions were activated (Henry et al, 2004). Inconsistent results were also obtained in the amygdala (Zobel et al, 2005;Conway et al, 2006).…”
Section: Downloaded Fromsupporting
confidence: 59%
“…39 It has been demonstrated that depression results in autonomic imbalance, with impaired parasympathomimetic functions. 40 Experimental findings also confirm that impaired cholinergic function may play a causal role in gut inflammation; disease activity index, macroscopic and histologic scores, myeloperoxidase activity, level of serum amyloid-P, and colonic tissue levels of IL-1b, interleukin-6 (IL-6), and TNF-a were increased significantly in vagotomized mice in DSS and hapten-induced colitis when compared with sham-operated mice that received DSS or the hapten. 41 These results suggest that vagal nerve is likely to exert a tonic inhibition on acute inflammation.…”
Section: Why Can Depression Negatively Influence the Course Of Ibd?supporting
confidence: 52%
“…Functional imaging studies in depressed humans indicate that metabolism and blood flow decrease in the sgACC/ ventromedial PFC in response to chronic treatment with antidepressant drugs, vagus nerve stimulation, or deep brain stimulation of the sgACC or anterior capsule (Mayberg et al, 1999(Mayberg et al, , 2005Drevets et al, 2002a;Van Laere et al, 2006;Nahas et al, 2007;Conway et al, 2006). Activity in the broader limbic-thalamo-cortical circuitry also decreases during effective treatment with antidepressant drugs or electroconvulsive therapy (Drevets et al, 2002a(Drevets et al, , 2004a.…”
Section: Antidepressant Treatment Effectsmentioning
confidence: 99%